2019
DOI: 10.21037/atm.2019.11.28
|View full text |Cite
|
Sign up to set email alerts
|

A deep learning system for identifying lattice degeneration and retinal breaks using ultra-widefield fundus images

Abstract: Background: Lattice degeneration and/or retinal breaks, defined as notable peripheral retinal lesions (NPRLs), are prone to evolving into rhegmatogenous retinal detachment which can cause severe visual loss. However, screening NPRLs is time-consuming and labor-intensive. Therefore, we aimed to develop and evaluate a deep learning (DL) system for automated identifying NPRLs based on ultra-widefield fundus (UWF) images.Methods: A total of 5,606 UWF images from 2,566 participants were used to train and verify a D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 23 publications
0
39
0
Order By: Relevance
“…Other retinal abnormalities, such as macro aneurysms and retinoblastoma, will be added in our future studies. Furthermore, because of the limitation of traditional fundus photographs with limited visible scope, 27 CARE is not able to identify peripheral retinal pathologies. In addition, only a few diseases were included in the performance comparison between CARE and the ophthalmologists and the tests with non-Chinese ethnicities and unseen camera types.…”
Section: Discussionmentioning
confidence: 99%
“…Other retinal abnormalities, such as macro aneurysms and retinoblastoma, will be added in our future studies. Furthermore, because of the limitation of traditional fundus photographs with limited visible scope, 27 CARE is not able to identify peripheral retinal pathologies. In addition, only a few diseases were included in the performance comparison between CARE and the ophthalmologists and the tests with non-Chinese ethnicities and unseen camera types.…”
Section: Discussionmentioning
confidence: 99%
“…The DLIFS was trained by a state-of-the-art deep convolutional neural network (CNN) architecture, InceptionResNetV2, which combines the architectural characteristics of ResNet and Inception, including skip connection and variable kernel sizes, and results in a more performant architecture than the two predecessors 38 . Our previous study also has demonstrated that the InceptionResNetV2 is the best algorithm for developing an AI system based on UWF images when compared to other three state-of-the-art algorithms (InceptionV3, ResNet50 and VGG16) 19 . Weights pretrained for ImageNet classification were applied to initialise the CNN architectures 39 .…”
Section: Methodsmentioning
confidence: 93%
“…Because retinal hard exudation is difficult to distinguish from drusen based on appearance alone and because cases with each of these conditions should be referred, we assigned them to the same group. Methods for developing a deep learning system to detect LDRB were described in our previous study 19 . For GON detection, images were classified into two categories: GON and non-GON.…”
Section: Methodsmentioning
confidence: 99%
“…With respect to the prediction of high myopia development by age 18 years, the model provided clinically acceptable accuracy over 3 years (the AUC ranged from 0.940 to 0.985), 5 years (the AUC ranged from 0.856 to 0.901), and even 8 years (the AUC ranged from 0.801 to 0.837), by predictors including age at examination, spherical equivalent (SE), and annual progression rate. In addition, Li et al 2019 , 2020 developed DL systems with high accuracy (over 96%) in detecting common comorbidities of high myopia, such as lattice degeneration, retinal breaks and retinal detachment, based on UWF images, which could further improve visual prognosis of myopia patients via timely medical intervention.…”
Section: Digital Innovations For Eye Diseasesmentioning
confidence: 99%